Streetcars and the shifting geographies of Toronto : a visual analysis of change - Doucet, Brian, 1980-; Doucet, Michael J. (University of Toronto Press, 2022)
"When looking at old pictures of the city of Toronto, it is clear that the city's urban, economic, and social geography has changed dramatically over the generations. Historic photos of Toronto's streetcar network offer a unique opportunity to examine how Toronto has been transformed from a provincial, industrial city into one of North America's largest and most diverse regions. Streetcars and the Shifting Geographies of Toronto studies Toronto's urban evolution through an analysis of photographs taken by streetcar enthusiasts, beginning in the 1960s. These photographers did not intend to record the urban form, function, or social geographies of the city; they were "accidental archivists" whose main goal was to photograph the streetcars themselves. But today, their images render visible the ordinary, day-to-day life in the city in a way that no one else did. These historic photographs show a Toronto before gentrification, globalization, and deindustrialization. Each image has been re-photographed to provide fresh insights into a city that is in a constant state of flux. With gorgeous illustrations, this unique book offers an understanding of how Toronto has changed, and the reasons behind these urban shifts. The visual exploration of historic and contemporary images from different parts of the city helps to explain how the major forces shaping the city affect its city form, functions, neighbourhoods, and public spaces."--